2021
DOI: 10.1093/bib/bbab056
|View full text |Cite
|
Sign up to set email alerts
|

A model for pH coupling of the SARS-CoV-2 spike protein open/closed equilibrium

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), causative agent of the coronavirus disease 2019 (COVID-19) pandemic, is thought to release its RNA genome at either the cell surface or within endosomes, the balance being dependent on spike protein stability, and the complement of receptors, co-receptors and proteases. To investigate possible mediators of pH-dependence, pKa calculations have been made on a set of structures for spike protein ectodomain and fragments from SARS-CoV-2 and other corona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…These groups are not predicted to contribute differentially to pH-dependence of locked, closed, and open forms. Next, D398 was proposed to couple to pH-dependence of closed (mostly unlocked) to open forms [36]. This result is replicated in the current larger study (Fig.…”
Section: Predicted Stabilisation Of Locked Forms and Destabilisation Of Closed And Open Forms From Ph 75 To Phsupporting
confidence: 79%
See 1 more Smart Citation
“…These groups are not predicted to contribute differentially to pH-dependence of locked, closed, and open forms. Next, D398 was proposed to couple to pH-dependence of closed (mostly unlocked) to open forms [36]. This result is replicated in the current larger study (Fig.…”
Section: Predicted Stabilisation Of Locked Forms and Destabilisation Of Closed And Open Forms From Ph 75 To Phsupporting
confidence: 79%
“…3c). Towards the C-terminal part of S2 are several histidines [25, 36], for which burial and predicted resistance to protonation from pH 7.5 to 5 leads to destabilisation in all sub-groups. Of more interest for differences between sub-groups are amino acids with acidic sidechains that have elevated p K a s and are predicted to be stabilising from pH 7.5 to 5, since destabilisation is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the D398 variant allows pH-dependence open/close equilibrium of the spike, which is coupled potentially to the impact of D614G mutation and linoleic acid-binding. This is also possibly linked to A570D mutation [34]. Also, it is reported that pH does not trigger the conformational changes of the spike protein from the "down" to the "up" state [36].…”
Section: Conformational Dynamics Analysis By Rmsdmentioning
confidence: 96%
“…In the recently reported mutations, those in UK, South Africa, Brazil and other countries, the stability also increased and claimed a stable evolution of the new variants. Studies have shown clearly that the environmental pH plays a key part in SARS-CoV-2 infection as demonstrated by the pH (6.3) requirement for virus entry and its genome release (pH < 6) endosomes along with pH of the export secretory pathway (pH 5.5) for newly assembled viruses [34,35]. pH variation with respect to SARS-CoV-2 variant cell entry and exit has been discussed.…”
Section: Conformational Dynamics Analysis By Rmsdmentioning
confidence: 99%
“…Previous reports have indicated that acidic amino acids play an essential role in pH-dependent binding (Roche et al 2006 ). Warwicker et al recently demonstrated that the SARS-CoV-2 spike protein trimer structures undergo a pH-dependent switch at acidic pH and that this involves E191, D985, and D398 acidic residues; this is thought to avoid immune surveillance of the open form of the receptor-binding domain of the S protein (Warwicker, 2021 ). Kumar et al demonstrated that the ionization state of the acidic residues at the active site of hexokinase B were responsible for the opening and closing of the cleft between the two domains at different pH ranges, thereby affecting the structure and function of the enzyme (Kumar et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%